2021
DOI: 10.3389/fpubh.2021.648009
|View full text |Cite
|
Sign up to set email alerts
|

How Australian Health Care Services Adapted to Telehealth During the COVID-19 Pandemic: A Survey of Telehealth Professionals

Abstract: Background: In Australia, telehealth services were used as an alternative method of health care delivery during the COVID-19 pandemic. Through a realist analysis of a survey of health professionals, we have sought to identify the underlying mechanisms that have assisted Australian health services adapt to the physical separation between clinicians and patients.Methods: Using a critical realist ontology and epistemology, we undertook an online survey of health professionals subscribing to the Australian Telehea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 15 publications
3
103
0
4
Order By: Relevance
“…Despite these challenges and modifications to clinical practice, most clinicians still reported a high degree of confidence in conducting telehealth assessments. A recent survey of Australian healthcare professionals on how they adapted to telehealth during the pandemic showed that confidence to use telehealth increased with practice ( Taylor et al, 2021 ). Prior to the COVID-19 pandemic, telehealth assessments for autism were largely viewed as an option for families living in regional and remote locations only, allowing them access to expert clinicians and reducing the cost of health care and additional travel for these families ( Reese et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges and modifications to clinical practice, most clinicians still reported a high degree of confidence in conducting telehealth assessments. A recent survey of Australian healthcare professionals on how they adapted to telehealth during the pandemic showed that confidence to use telehealth increased with practice ( Taylor et al, 2021 ). Prior to the COVID-19 pandemic, telehealth assessments for autism were largely viewed as an option for families living in regional and remote locations only, allowing them access to expert clinicians and reducing the cost of health care and additional travel for these families ( Reese et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In these early months of the pandemic, politicians, policymakers, and the lay press across different countries and regions all emphasized the role of new modalities such as video and e-consultations in this unprecedented service change [29][30][31][32][33]. But despite this focus on the novel, the reality in most countries was that most remote consultations-especially in primary care-occurred using the old-fashioned telephone [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reported benefits of telehealth models, including high patient satisfaction, equivalent clinical outcomes and cost-effectiveness, [1][2][3][4][5][6] its adoption into mainstream clinical practice had been slow prior to the COVID-19 pandemic. 7,8 Much of the literature investigating this highlights that while adoption can be hindered by access to technological infrastructure, 7,9 acceptance by front-line staff ultimately determines the success or failure of implementation efforts. 10,11 As such, key practicalities need to be met when establishing a telehealth service, including telehealth platform selection, environmental set-up, patient selection and suitability, as well as ethical, operational and professional considerations.…”
Section: Introductionmentioning
confidence: 99%